Experimental Cryoablation of Thyroid Gland with Propilthiouracyl-Induced Diffuse Hyperplasiae - Pobielienskyi, Kostiantyn; Pakhomov, Oleksandr; Gurina, Tetyana; Pobielienska, Liliia; Legach, Ievgen; Bozhok, Galyna (Problems of Cryobiology and Cryomedicine, 2021)
Cryoablation under endoscopic control is considered to be a promising approach in therapy of benign nodules of thyroid gland (TG). However, pathologically altered TG tissue differs in thermal conductivity and heat capacity from normal one, therefore the model experiments in animals are necessary to determine the cryoablation parameters. In this research, the changes of temperature during cryoablation of experimental rat TG under normal conditions and the one with propylthiouracil (PTU)-induced diffuse hyperplasia (DH) were comparatively assessed. TG was cryo-ablated in rats, previously received a 0.1% PTU solution within 90 days, using a copper cryoprobe, cooled to liquid nitrogen temperature. The process was controlled using thermocouples placed at different distances from the iceball. Differences between thermograms of intact TG tissue and the samples with PTU-induced DH were established. To achieve the destruction effect of TG with DH to a depth of more than 1 mm, the need of implementing two freeze-thaw cycles with 120-second cryoprobe exposure was proven. Probl Cryobiol Cryomed 2021; 31(2): 168–179